2005
DOI: 10.1111/j.1365-3180.2004.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐dispersal seed predation of non‐target weeds in arable crops

Abstract: Summary Field experiments were conducted to quantify the natural levels of post‐dispersal seed predation of arable weed species in spring barley and to identify the main groups of seed predators. Four arable weed species were investigated that were of high biodiversity value, yet of low to moderate competitive ability with the crop. These were Chenopodium album, Sinapis arvensis, Stellaria media and Polygonum aviculare. Exclusion treatments were used to allow selective access to dishes of seeds by different pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 32 publications
4
63
1
Order By: Relevance
“…Conservation biological control is often not targeted directly at the pest, as the abundance may lead to enhanced weed suppression in many agricultural systems is widely accepted ( Gallandt et al, 2005 ;Westerman et al, 2005 ). While in some instances seedeating carabid abundance has been positively related to seed predation level ( Menalled et al, 2007 ) or change in the weed seedbank , other studies have failed to demonstrate such links ( Davis and Raghu, 2010 ;Gaines and Claudio Gratton, 2010 ;Mauchline et al, 2005 ;Saska et al, 2008 ). The lack of a clear numerical response of weed predation to seed-eating carabid abundance possibly refl ects differences in the species present in the experiment, and insuffi cient consideration may have been given to the diversity of trophic and functional roles within this group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation biological control is often not targeted directly at the pest, as the abundance may lead to enhanced weed suppression in many agricultural systems is widely accepted ( Gallandt et al, 2005 ;Westerman et al, 2005 ). While in some instances seedeating carabid abundance has been positively related to seed predation level ( Menalled et al, 2007 ) or change in the weed seedbank , other studies have failed to demonstrate such links ( Davis and Raghu, 2010 ;Gaines and Claudio Gratton, 2010 ;Mauchline et al, 2005 ;Saska et al, 2008 ). The lack of a clear numerical response of weed predation to seed-eating carabid abundance possibly refl ects differences in the species present in the experiment, and insuffi cient consideration may have been given to the diversity of trophic and functional roles within this group.…”
Section: Introductionmentioning
confidence: 99%
“…Carabids might alter their behaviour, in response to the risk of intra-guild predation, by lowering their level of activity or by leaving prime foraging locations, in order to reduce their individual risk ( Prasad and Snyder, 2004 ;Guy et al, 2008 ). Finally, several studies suggest the existence of shifts in diet, in seed-eating carabids, which depend upon the prevailing conditions ( Marino et al, 2005 ;Mauchline et al, 2005 ;Brooks et al, 2012 ); indeed fi eld surveys indicate that specifi c spatial associations vary in time ( Trichard et al, 2014 ). Such prey switching has been found for carabids that can, for example, feed on weed seeds and animal pests such as slugs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and modeling studies have clearly shown that predation significantly affects weed seed demographics (Mauchline et al 2005 . Meiss et al (2010) reported that the vegetative cover influences weed-seed predators by altering the habitat quality.…”
Section: Weed Seed Destructionmentioning
confidence: 99%
“…In the temperate zone, these are the most important seed predators (Honek et al, , 2005 in intensively managed agricultural landscapes (Saska et al, 2014). Granivorous carabids are important pre-and postdispersal weed seed predators, and in terms of agricultural ecosystem services are biological control agents of weeds (Mauchline et al, 2005;Jacob et al, 2006;Gaines & Gratton, 2010;Kulkarni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%